PERENCANAAN PEMBUATAN MEDIA PEMBELAJARAN MATA PELAJARAN SIMULASI DIGITAL DI SMK NEGERI 5 SURAKARTA - Retnoningsih, Dwi; Al Haris, Firdhaus Hari Saputro; Wardani, Dwi Esti (JURNAL GAUNG INFORMATIKA, 2015)
Learning media is one of important component in teaching and learning activities. The use of media in learning activities to make learning and teaching more enjoyable.Students will feel interested in learning that will enhance the learning results. The problem is the media that is used for this is still the conventional so that learning andteaching becomes monoton,teachers are less able to develop and students to be difficult to understand and accept the lesson .The purpose of this research was to design media based learning multimedia interactive and informative in SMK Negeri 5 Surakarta.This research used data collection methods (the necessary data obtained by the method of observation and documentation), and the Waterfall method for systemdevelopment. This research resulted in a multimedia-based learning program that can be directly used by teachers as a tool in the learning process.